2018
DOI: 10.3389/fimmu.2018.02829
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells Respond to Candida albicans Infections and Modulate Macrophages Phagocytosis of the Fungus

Abstract: Mast cells (MCs) are long-lived immune cells widely distributed at mucosal surfaces and are among the first immune cell type that can get in contact with the external environment. This study aims to unravel the mechanisms of reciprocal influence between mucosal MCs and Candida albicans as commensal/opportunistic pathogen species in humans. Stimulation of bone marrow-derived mast cells (BMMCs) with live forms of C. albicans induced the release of TNF-α, IL-6, IL-13, and IL-4. Quite interestingly, BMMCs were abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…Activated mast cells enhance macrophage functionality by improving their crawling ability and chemotaxis in response to C. albicans stimulation (De Zuani et al . 2018 ). Meanwhile, resting mast cells inhibit the phagocytosis of C. albicans by macrophages, which suggests a role for mast cells in the maintenance of commensalism (De Zuani et al .…”
Section: The Hostmentioning
confidence: 99%
“…Activated mast cells enhance macrophage functionality by improving their crawling ability and chemotaxis in response to C. albicans stimulation (De Zuani et al . 2018 ). Meanwhile, resting mast cells inhibit the phagocytosis of C. albicans by macrophages, which suggests a role for mast cells in the maintenance of commensalism (De Zuani et al .…”
Section: The Hostmentioning
confidence: 99%
“…A dual role of IL-9 has been reported in gastrointestinal candidiasis [105]. Studies in mice showed that IL-9 is likely to modulate vaginal response to Candida in a time-dependent manner, initially favoring inflammation via NLRP3 activation and then tolerance to the fungus by stimulating IL-1Ra production, mast cell (MC) engagement and macrophage crawling [106,107]. Interestingly, as the IL-9/MC axis contributes to chronic allergic inflammation [108] and is associated in a sex-specific manner with IgE levels in cystic fibrosis [109], it may lead to the hypothesis that VVC is an allergic reaction to the ability of Candida-specific IgE and prostaglandin E2 (PGE 2 ) to inhibit vaginal cell-mediated immune response [110].…”
Section: Immunology: Rvvc As An Autoinflammatory Diseasementioning
confidence: 99%
“…Phagocytosis is at once an ancient and physiologically fundamental mechanism for safeguarding host health against microbial invasion 27,28 . The dynamic and intricate nature of the protein machinery at work during phagocytosis necessitates ever better scope and resolution in proteomic analysis to provide a refined understanding of the process at the systems level.…”
Section: Discussionmentioning
confidence: 99%